Mères sans mari. Filles-mères et abandons d’enfants (Paris, 1870-1920) - Antoine Rivière (Genre & Histoire)
From the beginning of the Third Republic to the close of the Great War, about 3,000 children were abandoned each year in Paris and taken in by the public care services (Assistance publique). In the vast majority of cases, the parents who gave up their off-spring were single mothers. Forsaken by the father of their child, some sought to hide their shame from their own parents; others responded to their families’ firm injunction to redeem the dishonour of their out-of-wedlock pregnancies. In all such cases unmarried mothers epitomized the figure of social abandonment. Their stories are those of feminine misery and the social infamy attached to single motherhood.